A case study on the operator allocation decision for TFT-LCD inspection and packaging process - Kuo, Yiyo; Yang, Taho (Journal of manufacturing technology management, 2006)
Purpose - Thin film transistor liquid crystal display (TFT-LCD) is the primary flat panel display (FPD) technology, which is quickly becoming pervasive in many applications including computers, mobile phones, TV monitors, and so on. The finished product of a TFT-LCD display device is called "module". A module is subject to a final inspection and packaging (I P) process before it is shipped to the customer. The I P operations are primarily manual and the present study seeks to focus on these. The I P process is strategically important since it directly impacts on both customer service and out-going quality levels. The operator allocation decision for I P operations determines the through-put of the I P line, and is a function of demand requirement, operator availability, and product dedication.Design methodology approach - This research proposes to solve the I P process operator allocation problem by mixed-integer programming formulations. A practical case study has been adopted for the empirical illustrations.Findings - Empirical results are promising. The potential improvement is ranging from 9 to 20 percent against the current practice at the case study company.Originality value - A structured experimental design shows the effectiveness and efficiency of the proposed formulations in solving the problem of the case study.